دراسة تاثير المرشحات السيراميكية على النمو البكتيري للماء المرشح / Studding The Effect of Ceramic Filters on Bacteria Growth for Filtered Water (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2017)
Ceramic water filtration is the process that makes use of a porous ceramic medium to filter microbes or other contaminants from water. The objective of this research is prepared ceramic water filter from available and inexpensive material. Ceramic bodies were formulated from kaolinite with two particle sizes,(45-63) µm for fine size and (105-150) µm for coarse size with add combustible materials (charcoal, carrot fiber) which act as pore-creating agent. The formulated ceramic bodies were shaped into filters (disk) slip casting technique, and then fired at (1100˚C). Some physical tests such as (apparent porosity, and permeability), in addition to biological tests have been studied, and the efficiency of filters to remove suspended solids materials has been calculated.